(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdhUGjG LeY hUjI ef ChUi jhUj Ch hUi jhUj, bGd aj GdUMGM(B: (3ChUjJ dg HTjA hChUjJ Edjg EPG LYdJg hUjc hGdGSe GdhUGjIs
(3BNQgG (B:s
(3BNQgG(B: (3dCfg eMchc HUMJg Edi GdehJ hhLg GdUMI hLhO GdebJVi hUOhQ GdYbO ef Cgdg aj eMdg hGfJaGA GdeGfY EP dGMb dZjQg GdBf aj QbHJgG hEfeG jJcTa Pdc YfO GdehJ ceG Yf GdJMQjQ GdUMjM Hgs
(3ebGHdI Ydi eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis